PENGARUH EFIKASI DIRI DAN SOFT SKILLS TERHADAP KESIAPAN KERJA MAHASISWA TINGKAT AKHIR - Aldo Febrianka; Muharam, Husni; Wufron, Wufron (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study investigates the impact of self-efficacy and soft skill competencies on the work readiness of final-year students in the Management Study Program at Garut University. The research employs a quantitative methodology with a descriptive design, involving 100 respondents selected from a predetermined population. Data were collected using questionnaires as the primary source, supplemented by secondary data from relevant literature. Data analysis was conducted using SPSS version 30. The findings indicate that self efficacy exerts a partial scientific impact on students' readiness to enter the professional world. Furthermore, both self-efficacy and soft skill competencies have a simultaneous positive impact on their overall readiness. High self-efficacy boosts students' confidence in navigating the dynamics of the professional environment, while strong soft skills enhance their ability to adapt, communicate, and collaborate effectively in a workplace. Therefore, strengthening self-efficacy and developing soft skills are identified as crucial factors in improving students' work readiness.